2020
DOI: 10.1186/s12914-020-00248-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of women from families of martyred individuals in the Kurdistan region of Iraq as a conflict area in the Middle East

Abstract: Background Quality of life (QOL) research develops data and insight into issues that pertain not only to the individual, but that can also apply to the population as a whole. This study aimed to analyze the QOL of Kurdish women from families of martyred individuals in the Kurdistan region of Iraq. Methods A cross-sectional study of 380 women from families of martyred individuals was conducted. All women were patients at the Medical Center of Martyr Families in Erbil City from January 2018 to April 2019. Data … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…e) Social and cultural factors Cultural factors including traditions, language and religion have contributed towards the failure of ehealth implementation due to restricted human interactions [25]. Iraqi and Middle Eastern individuals are profoundly impacted by their culture and there is an inclination towards physical interaction rather than virtual contact [26]. f) Medication safety [27] Stated that medication safety consists of two main e-health elements.…”
Section: D) Human Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…e) Social and cultural factors Cultural factors including traditions, language and religion have contributed towards the failure of ehealth implementation due to restricted human interactions [25]. Iraqi and Middle Eastern individuals are profoundly impacted by their culture and there is an inclination towards physical interaction rather than virtual contact [26]. f) Medication safety [27] Stated that medication safety consists of two main e-health elements.…”
Section: D) Human Factorsmentioning
confidence: 99%
“…Group 3, the rules related to factors (testBPS=PreHypn, chol=high) are extracted in (4,20,22,26,28) associated to HeartDisease=yes. The highest confidence is attributed to 0.94 in rule 4 and followed by the confidence (0.88, 0.86, 0.79, 0.71) of the associated rules to this correlation, which show a strong relationship between high blood pressure and high cholesterol.…”
Section: Mining Seci Model Secicarmentioning
confidence: 99%
“…It has been described that war times, post war, or natural disasters, lead to biopsychosocial issues and have an impact on the quality of life (QoL) of those who go through such events [25][26][27][28][29]. However, research on the impact of collective violence on health has been scarce and relatively disciplinary fragmented and has not considered all aspects of human beings.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6] No study has focussed on the Iraqi general population even though a few have reported QOL among people with diseases, refugees and internally displaced persons owing to military and political conflicts in the country. [7][8][9] The current study was planned to fill the gap by determining the QOL of the general adult people in an urban community, and to evaluate the effect of sociodemographic factors on people's QOL.…”
Section: Introductionmentioning
confidence: 99%